The educational inspection in the superior conservatories of music in Galicia: present and future - Polo Cal, Rosalía; Vázquez Rodríguez, Rubén (Avances en Supervisión Educativa, 2022)
The main objective of this work is to carry out a deep reflection on the perspective of the function and competences of the educational inspection in the Galicia higher music conservatories, taking into account the context of the educational advance of the special regime teaching and its social consideration, all with a purpose of improving the inspective intervention in this type of schools centers, regarding the collection and analysis of exhaustive and rigorous information, in accordance with current regulations, in coexistence with the real demands and needs of these centers, and adding the challenge of adapting the latter to reality of the conservatories in terms of: the academic training and professional preparation of their students, their diversity, characteristics and internationalization; the continuous academic and professional training of its teaching staff, and, finally and above all, to the contextualization of the teachings that these centers impart in a society that is in permanent and constant change, attending to their demands while respecting the framework of current regulations. In this way, the purpose of this article is to analyze the role of the Educational Inspection in Music Conservatories, as centers whose uniqueness requires a specific intervention necessarily adapted to the teachings imparted.